2020
DOI: 10.1371/journal.pcbi.1007195
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling reveals kinetic heterogeneity in post-replication DNA methylation

Abstract: DNA methylation is a heritable epigenetic modification that plays an essential role in mammalian development. Genomic methylation patterns are dynamically maintained, with DNA methyltransferases mediating inheritance of methyl marks onto nascent DNA over cycles of replication. A recently developed experimental technique employing immunoprecipitation of bromodeoxyuridine labeled nascent DNA followed by bisulfite sequencing (Repli-BS) measures post-replication temporal evolution of cytosine methylation, thus ena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…DNMT1 and DNMT3B both methylate processively along DNA strands whereas DNMT3A methylates in a distributive manner but can form multimers along the DNA fibre 49 . A computational analysis of DNA re-methylation dynamics suggests these processes are required to explain the observed rates of DNA re-methylation following replication 50 . The efficiency of DNMTs is also influenced by bases surrounding CpGs in vitro 51,52 and in vivo 53 .…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 and DNMT3B both methylate processively along DNA strands whereas DNMT3A methylates in a distributive manner but can form multimers along the DNA fibre 49 . A computational analysis of DNA re-methylation dynamics suggests these processes are required to explain the observed rates of DNA re-methylation following replication 50 . The efficiency of DNMTs is also influenced by bases surrounding CpGs in vitro 51,52 and in vivo 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its unique features, MethylTransition has two technical limitations. First, due to the high dropout rates of public scBS-seq data, MethylTransition relies on the assumption that the activity levels of DNA methylation-modifying enzymes in a cell are constant across the genome, which is inconsistent with numerous reports that both sequence and epigenetic features affect the activity of these enzymes [ 25 , 46 49 ]. This limitation could be partially resolved by applying this framework to a subset of promoters with similar sequence or epigenetic features.…”
Section: Discussionmentioning
confidence: 99%
“…McGovern et al and von Meyenn et al further incorporated 5-hydroxymethylcytosine (5hmC) into models to reflect the contribution of active demethylation to the DNA methylation state transition [ 23 , 24 ]. Recently, Busto-Moner et al enabled genome-wide quantification of subcell cycle kinetics of methylation maintenance using replication-associated bisulfite sequencing (Repli-BS-seq) data [ 25 ]. Researchers have proposed two types of methods to estimate the parameters of the models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of repli-BS data also supports that CpG re-methylation occurs with very different speeds in distinct genomic regions, which correlate with the local density of CpGs. Mathematical modelling revealed that the kinetics of restoration between the neighboring CpG motifs in the genome is correlated ( 137 ), suggesting that either DNMT1 is processive through stretches of chromatinized template, or that the recruitment of DNMT1 in nearby loci is coregulated.…”
Section: Introductionmentioning
confidence: 99%